DEVELOPMENT OF VIRTUAL SMART HUMAN EXCRETORY SYSTEM LEARNING MEDIA BASED ON ARTICULATE STORYLINE 3 TO INCREASE STUDENT MOTIVATION AND LEARNING - Mulhayati Mulhayati; Zainal Abidin Abidin; Asep Ginanjar Arip (Indonesian Journal of Learning and Instruction, 2024)
COVID-19 pandemic in Indonesia caused a change in the system of conventional learning activities to distance learning. Some of the obstacles to the distance learning system from the results of the questionnaire analysis of learning media needs for some students and teachers are the low motivation of students in participating in PJJ so that student learning outcomes are also low. Researchers have the idea that PJJ is done by utilizing interactive multimedia which is expected that students do not feel monotonous in participating in PJJ which has an impact on increasing student learning outcomes. Articulate Storyline 3 is one of the multimedia authoring tools used to create interactive learning media with content in the form of a combination of images, text, sound, graphics, video, and animation. This research method adapts the ADDIE development model. The subjects of this study were students of class VIII G SMPN 7 Cirebon City totaling 36 students. The results of the analysis of this study indicate that the interactive learning media virtual smart human excretory system based on articulate storyline 3 on the excretory system material is feasible to use because it can increase students' learning motivation, the average normalized gain index from pretest to posttest is 0.70 high category and the results learning is 0.73 with a high category, and the level of functioning of the virtual smart human excretory system learning media is at a functioning level with a very effective category.